The harsh reality of Ukraine's fiscal arithmetic - Marek Dabrowski (Bruegel, 2015)
Ukraine is struggling with both external aggression and the dramatically poor shape of its economy. The pace of political and institutional change has so far been too slow to prevent the deepening of the fiscal and balance-of-payments crises, while business confidence continues to be undermined. Unfortunately, the 2015 International Monetary Fund Extended Fund Facility programme repeats many weaknesses of the 2014 IMF Stand-by Arrangement: slow pace of fiscal adjustment especially in the two key areas of energy prices and pension entitlements, lack of a comprehensive structural and institutional reform vision, and insufficient external financing to close the expected balance-of-payments gap and allow Ukraine to return to debt sustainability in the long term. The reform process in Ukraine must be accelerated and better managed. A frontloaded fiscal adjustment is necessary to stabilise public finances and the balance-of-payments, and to bring inflation down. The international community, especially the European Union, should offer sufficient financial aid backed by strong conditionality, technical assistance and support to Ukraine's independence and territorial integrity.
Keywords: 330